Yield under great persuasion - Rowland, Alexandra ([Publisher not identified], 2024)
"A cozy M/M romantasy. Tam Becket has hated Lord Lyford since they were boys. The fact that he's also been sleeping with the man for the last ten years is irrelevant. When they were both nine years old, Lyford smashed Tam's entry into the village's vegetable competition. Nearly twenty years later, Tam hasn't forgiven him. No one understands how deeply he was hurt that day, how it set a pattern of disappointments and small misfortunes that would run through the rest of his life. Now Tam has reconciled himself to the fact that love and affection are for other people, that the gods don't care and won't answer any of his prayers (not even the one about afflicting Lyford with a case of flesh-eating spiders to chew off his privates), and that life is inherently mundane, joyless, and drab. And then, the very last straw: Tam discovers that Lyford (of all people!) bears the divine favor of Angarat, the goddess Tam feels most betrayed and abandoned by. In his hurt and anger, Tam packs up and prepares to leave the village for good. But the journey doesn't take him far, and Tam soon finds himself set on a quest for the most difficult of all possible prizes: Self care, forgiveness, a second chance... and somehow the unbelievably precious knowledge that there is at least one person who loves Tam for exactly who he is-and always has."--Amazon.com.